Interplay of Topology, Localization, and Non-Hermiticity in Low-dimensional Systems realized through Electrical Circuits - Halder, Dipendu (My University, 2026)
Topology has revolutionized the understanding of condensed matter systems by revealing phases of matter characterized by global invariants rather than local order parameters. The inclusion of non-Hermiticity, arising from gain, loss, and non-reciprocal interactions, enriches this framework by introducing unique phenomena such as exceptional points, non-Hermitian skin effects, generalized Brillouin zones, and modified bulk boundary correspondence. In parallel, topolectrical circuits have emerged as a versatile and experimentally accessible platform for realizing and probing such topological systems.
Basu, Saurabh